2001
DOI: 10.1590/s1516-89132001000200014
|View full text |Cite
|
Sign up to set email alerts
|

Histological analysis of the callogenesis and organogenesis from root segments of Curcuma zedoaria Roscoe

Abstract: Callus was induced from root segments taken from in vitro grown plants of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
1
7
1
3
Order By: Relevance
“…11). Unlike the reported for P. cincinnata, in Curcuma zedoaria (Melo et al 2001), indirect organogenesis was observed in root segments, although the cellular divisions for callus formation occurred in the cortical parenchyma. Likewise, Peres et al (2001) observed in anatomical analysis of in vitro wild tomato (Lycopersicon peruvianum, L. chilense and L. hirsutum) the formation of buds in the roots, which can also occur direct or indirectly, depending on the genotype used.…”
Section: Root Segments and Seedlingscontrasting
confidence: 83%
“…11). Unlike the reported for P. cincinnata, in Curcuma zedoaria (Melo et al 2001), indirect organogenesis was observed in root segments, although the cellular divisions for callus formation occurred in the cortical parenchyma. Likewise, Peres et al (2001) observed in anatomical analysis of in vitro wild tomato (Lycopersicon peruvianum, L. chilense and L. hirsutum) the formation of buds in the roots, which can also occur direct or indirectly, depending on the genotype used.…”
Section: Root Segments and Seedlingscontrasting
confidence: 83%
“…The calli were yellowish and nodular with morphogenic aspects. Plant can be regenerated from these calli by indirect organogenesis (Mello et al, 2001). According to these authors, histological analysis revealed that callus was formed from hypertrophied cortical parenchyma cells of the explant.…”
Section: Callus Inductionmentioning
confidence: 99%
“…The key to technical and economic feasibility rests on the ability to induce and select genetically stable whole plants or cell cultures that overproduce specific chemicals and the development of scale-up technology that exploits the biological capabilities of plant cells and promotes efficient production (Whitaker & Evans, 1987). To reach these goals, several reports of in vitro culture of species from the Zingiberaceae family have been published (Illg & Faria, 1995;Sharma & Singh, 1997;Borthakur et al, 1998, Shirin et al, 2000Mello et al, 2001;Salvi et al, 2002). This work reports the feasibility of the utilization of tissue culture techniques to establish a protocol for micropropagation and cell suspension culture of Curcuma zedoaria Roscoe, which can be a source for secondary metabolites production.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is known that high concentrations of BA usually suppress plant regeneration. 27) The fact that the use of apical double node microshoots resulted in root absence suggests that the addition of NAA was not able to reverse the negative effects of BA on root formation, as in other species. 27,28) The control was the only treatment that promoted the elongation and rooting of the explants.…”
Section: Resultsmentioning
confidence: 98%